1977
DOI: 10.1029/gl004i011p00507
|View full text |Cite
|
Sign up to set email alerts
|

Aftershocks of the 8 July, 1975 Canal de las Ballenas, Gulf of California, Earthquake

Abstract: A Ms = 6.5 earthquake occurred on 8 July, 1975 in the northern part of the Gulf of California. The calculated seismic moment is 2 × 1025 dyne‐cm. This event occurred in a region of particular interest since the position of the transform fault in this region was not well known and had been locked for at least 20 years. Over 180 aftershocks were located along a zone 54 Km long, 10 Km wide and 10‐15 Km deep running between Baja California and Isla Angel de la Guarda. The depth of the aftershock zone is somewhat g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Our coseismic fault models have a rupture depth of 13 km, equivalent within uncertainties to the seismic estimates of 10-15 km for the base of earthquake nucleation along transforms in the Gulf of California [Munguia et al, 1977;Goff et al, 1987;Castro et al, 2010Castro et al, , 2011Sumy et al, 2013] but deeper than our estimates for the interseismic fault locking depth. Agreement between both parameters is not expected, Journal of Geophysical Research: Solid Earth 10.1002/2015JB011959 because the two approaches estimate the depth of the brittle-ductile transition zone over different time scales.…”
Section: Coseismicsupporting
confidence: 73%
See 1 more Smart Citation
“…Our coseismic fault models have a rupture depth of 13 km, equivalent within uncertainties to the seismic estimates of 10-15 km for the base of earthquake nucleation along transforms in the Gulf of California [Munguia et al, 1977;Goff et al, 1987;Castro et al, 2010Castro et al, , 2011Sumy et al, 2013] but deeper than our estimates for the interseismic fault locking depth. Agreement between both parameters is not expected, Journal of Geophysical Research: Solid Earth 10.1002/2015JB011959 because the two approaches estimate the depth of the brittle-ductile transition zone over different time scales.…”
Section: Coseismicsupporting
confidence: 73%
“…About~90% of the full North America-Pacific plate relative motion rate (approximately 43-47 mm/yr) is accommodated along the Gulf of California [DeMets et al, 1990[DeMets et al, , 1994DeMets and Dixon, 1999;Dixon et al, 2000a;Plattner et al, 2007Plattner et al, , 2009. Because of the submarine setting, however, crustal deformation studies have largely been limited to the interpretation of faulting processes that occur over short time scales in the seismogenic zone [Munguia et al, 1977;Goff et al, 1987;Rebollar et al, 2001;Rodriguez-Lozoya et al, 2008;Castro et al, 2010Castro et al, , 2011Sumy et al, 2013;Lopez-Pineda et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…However, the assumed fault width of 12 km is also based on the hypocentral distribution of the previous 1975 earthquake sequence. Munguía et al (1977) found that the aftershocks of the 1975 Canal de Ballenas earthquakes were located up to 10-15 km deep. The rupture area thus Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…2). For instance, on 8 July 1975 an event with M s 6.5 occurred west of the island Angel de la Guarda (Munguía et al, 1977). Moderate magnitude earthquakes have also occurred in this region to the north, in the lower Delfin basin, on 26 November 1997 (M 5.5) and south of Angel de la Guarda island on 12 November 2003 (M w 5.4) and 24 September 2004 (M w 5.8).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation